Effects of supplemental calcium and vitamin D on tight‐junction proteins and mucin‐12 expression in the normal rectal mucosa of colorectal adenoma patients. Issue 7 (2nd April 2019) - Mandle, Hannah B.; Jahan, Ferdous A.; Bostick, Roberd M.; Baron, John A.; Barry, Elizabeth L.; Yacoub, Rami; Merrill, Julia; Rutherford, Robin E.; Seabrook, March E.; Fedirko, Veronika
Abstract: The physical gut barrier, comprised of a thick mucus layer and the epithelium, plays an important role in defense against microbes and foreign antigens. Calcium and vitamin D may be involved in maintaining the integrity of the intestinal mucosal barrier, the dysfunction of which may lead to endotoxemia and inflammation, and contribute to colorectal carcinogenesis. We investigated supplemental calcium (1200 mg, daily) and/or vitamin D3 (1000 IU daily) effects on intestinal barrier function‐related biomarkers in a subset of 105 participants from a large colorectal adenoma recurrence chemoprevention clinical trial. We assessed expression of the tight junction proteins claudin‐1 (CLDN1), occludin (OCLD), and mucin‐12 (MUC12) in the normal‐appearing colorectal mucosa using standardized, automated immunohistochemistry and quantitative image analysis. Following 1 year of treatment, in the calcium relative to the no calcium group, the CLDN1, OCLD, and MUC12 expression increased by 14% ( P  = 0.17), 23% ( P  = 0.11), and 22% ( P  = 0.07), respectively. In secondary analyses, the estimated calcium treatment effects were greater among participants with baseline serum 25‐OH‐vitamin D concentrations below the median value of 22.69 ng/mL (CLDN1: 29%, P  = 0.04; OCLD: 36%, P  = 0.06; MUC12: 35%, P  = 0.05). There were no biomarker expression changes in the vitamin D3 alone group; however, modest increases were found in the combined calcium/vitamin D3 group. At baseline, obesity, history of a sessile‐serrated adenoma, colorectal MIB‐1/Ki‐67 expression, and a family history of colorectal cancer were associated with CLDN1, OCLD, and MUC12 expression. Our study supports continued investigation of factors that could affect intestinal mucosal barrier integrity relevant to colorectal carcinogenesis.